A Technology of Expertise: EU Financial Services Agencies - Michelle Everson (London School of Economics and Political Science (LSE), European Institute, 2012)
The collapse of Lehman Brothers in 2008 ushered in a financial crisis whose ramifications are still being felt. Within the EU, collapse not only led to a change in regulatory rhetoric, emphasising the need to secure the stability of EU money markets, but also to a significant widening and deepening of technocratic supervisory structures for European financial services. This paper accordingly investigates the newly established European System for Financial Supervision and, in particular, semi-autonomous EU agencies for banking, insurance and securities, for its ability to provide robust regulation and supervision within Europe. However, it analyses this increase in technocratic governance at supranational level in light of the worrying question of whether it has undermined capacity for political action within Europe. At a time when readily-apparent failings in established technocratic governance in Europe (monetary union) have led only to more technocratisation (proposed fiscal union), perhaps to the point of systemic collapse, the general European trend to expert-led and evidence-based supervision must be doubted; not simply because it has failed on its own terms, but also because it has established a technology of expertise, or dominant rationality, which further encourages abdication of political responsibility for economic crisis.
Keywords: 330